Design of wideband Rotman lens for wireless applications - Mohammed K. Al-Obaidi; Ezri Mohd; Noorsaliza Abdullah; Samsul Haimi Dahlan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
An electrically steerable beam is an essential standard in the recent wireless application in order to increase the gain and reduce the interference. However, high performance of amplitude besides low phase error difficult to achieve without indicators are used to set lens parameters to desired optimum performance design level. In this paper, the introduced microstrip lens has examined a comprehensive explanation for parameters and indications amid a full wave structure methodology. Further, Phase and energy coupling between excited ports and received ports besides phase error and its relation with the lens parameters design are explained in detailed.  A wideband beamforming network based on a printed microstrip Rotman lens with a ±26o scanning angle was designed in this study. The designed lens operates at 2.45 GHz with 592 MHz bandwidth. The lens consists of five switchable ports (input ports) with four output ports that connected to the microstrip patch antennas. The five switchable ports were used to realize the scanning beams angle in the azimuth plane.  The proposed model is simulated by CST Microwave Studio and fabricated on FR-4 with 1.565 mm thickness and 4.2 permittivity.  A good agreement between simulation and measurement results were achieved.